Patient access to psychiatric records: the patients' view. - Parrott, J (1988)
The passing of legislation relating to subject access to personal health data has been accompanied by concern about the possible harmful effects of this development on patients. Despite the lack of substantive evidence psychiatric patients have been regarded as the group most at risk. This study investigates the subjective views of patients on access to records on two psychiatric wards.